Shock Waves in the Treatment of Muscle Hypertonia and Dystonia - Mori, Laura (Hindawi Publishing Corporation, 2014)
Since 1997, focused shock waves therapy (FSWT) has been reported to be useful in the treatment of muscle hypertonia and dystonia. More recently, also radial shock wave therapy (RSWT) has been successfully used to treat muscle hypertonia. The studies where FSWT and RSWT have been used to treat muscle hypertonia and dystonia are reviewed in this paper. The more consistent and long lasting results were obtained in the lower limb muscles of patients affected by cerebral palsy with both FSWT and RSWT and in the distal upper limb muscles of adult stroke patients using FSWT. The most probable mechanism of action is a direct effect of shock waves on muscle fibrosis and other nonreflex components of muscle hypertonia. However, we believe that up to now the biological effects of shock waves on muscle hypertonia and dystonia cannot be clearly separated from a placebo effect.